Electrodynamics an introduction including quantum effects - Muller-Kirsten, Harald J. W. (New Jersey World Scientific, 2004)
An extensive text on electrodynamics with detailed explanations and calculations. One hundred worked examples have been incorporated, making the book suitable also for self-instruction. Apart from all traditional topics of Maxwell theory, the book includes the special theory of relativity and the Lagrangian formalism and applications; the text also contains introductions to quantum effects related to electrodynamics, such as the Aharonov-Bohm and the Casimir effects. Numerous modern applications in diverse directions are treated in the examples.
Keywords: Electrodynamics; Quantum electrodynamics